DRY MATTER UTILIZATION AND ECOLOGICAL EFFICIENCIES IN LARVAE OF A PYRALID MOTH, DIAPHANIA INDICA SAUNDERS (LEPIDOPTERA) - GOEL, SHUBHRA; PANDEY, K. C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Feeding experiment on immature stages of D indica have been elaborated to discuss the fi utilization, ecological efficiencies and producer-consumer link on dry matter in a primary c. sumer. On an average 186.72 mg was the total ingested food resulting into 9.88% of the tiss growth in four larval stages. The AD had been the landmark of nutritional quality where ECD as the net growth efficiency for transforming assimilated food into the caterpillar's bioma CI and GR with poor values are suggestive for the suitability of the food on which a herbivo has fed The most significant role of the herbivore had been to process the accumulated part the food to different trophic levels in a food chain.